Neurodevelopmental Outcomes of Very-Low-Birth-Weight Infants without Severe Brain Lesions and Impact of Postnatal Steroid Use: A Single-Center Korean Study - Mun Hui Jeong; Seong Hee Jeong; Su Jeong Park; Narae Lee; Mi-Hye Bae; Kyung-Hee Park; Shin-Yun Byun; Choongrak Kim; Young Mi Han (Korean Society of Neonatology, 2022)
Purpose We used the Bayley Scales of Infant and Toddler Development (BSID)-III to analyze the incidence and risk factors of developmental delay in very-low-birth-weight infants without severe brain lesions. We further examined the correlation between the cumulative dexamethasone dose and developmental assessment results. Methods We retrospectively analyzed data of preterm infants (birth weight <1,500 g) admitted to our neonatal intensive care unit between January 2014 to December 2020. The BSID-III scores obtained between the corrected ages of 12 and 24 months and after 24 months were analyzed. Developmental delay was defined as a composite score of <85 for the cognition, language, and motor domains. Univariate and multivariate analyses of developmental delay risk factors and developmental changes from the first to second BSID-III were performed. Correlations between the accumulated dexamethasone dose used for bronchopulmonary dysplasia (BPD) and the first and second test scores were analyzed. Results Seventy-one and thirty-six infants completed the first and second tests, respectively. In both tests, developmental delay was most commonly observed in the language domain (26.8%, 47.2%). In multivariate analysis, mild BPD was identified as a developmental delay risk factor (P<0.05), whereas prenatal steroid use reduced the developmental delay risk (P<0.05). All domain scores were lower in the second test than in the first test. The cognition and language domain scores in the second test decreased with increasing cumulative dexamethasone doses. Conclusion Very-low-birth-weight infants typically experience language delay, which can persist as they age.